A Case of Bronze Turkey Twins Developing from Hatching. Issue 2 (24th December 2014) - Damaziak, K; Michalczuk, M; Zdanowska‐Sąsiadek, Ż; Niemiec, J
Contents A double‐yolked egg that was laid by an 11‐month‐old bronze turkey hen on 2 April, 2013 was reported. The presented case of developing turkey twin embryos is the first ever described case for this species. The egg weighed 125 g and had 74.6 mm in length and 53.0 mm in width. The embryos died between the 23rd and 24th day of incubation. Both twin 1 and twin 2 were fully developed with body weights of: 37.7 g and 40.3 g, respectively. The likely causes of death include inappropriate arrangement of embryos and insufficient gas exchange in the last period of incubation. The embryos were arranged along the long axis of the egg, one underneath the other, and were closely adhering to one another. The twins were different in plumage pigmentation. In twin 1, a spontaneous mutation of plumage pigmentation (B) was observed, whereas twin 2 showed appropriate pigmentation (b+) in respect to parents.